UCAO (UNILATERAL CEREBRAL ARTERY OCCLUSSION) METHOD INCREASES THE LEVEL OF MMP- 9 BRAIN TISSUE IN RATS MODEL OF ISCHEMIC STROKE - Indra, Muhamad Rasjad; Gasmara, Cakra Parindra (Malang Neurology Journal, 2016)
Background. UCAO (Unilateral Cerebral Artery Occlusion) is a stroke induction method by ligating miceâsÂ carotid artery for 45 minutes. Thus giving a hypoxic condition similar to stroke attacks to human. This method is less complicated and far more efficient. MMP-9 is a stroke marker which is assayed by ELISA from the blood of test animal.Objective. To prove UCAO method is capable to raise MMP-9 concentration in miceâs blood.Methods. This research was an experimental laboratory research with post-test only controlled group design. 8 male rats (8-10 weeks) were divided into 2 groups. A day after the treatment group had been induced to stroke, both group were tested to measure the MMP-9 blood concentration through ELISA.Results. In this research, UCAO method had increased MMP-9 blood concentration in treatment group, compared to the control group. It is proved by the statistic tests, Mann-Whitney and Kruskal-Wallis, which showed a significant increase in treatment group (p < 0.05).Conclusion. UCAO method is accepted as a method to create an ischemic stroke mice model.